THE INFLUENCE OF QUALITY OF WORK LIFE AND ORGANIZATIONAL CULTURE ON LECTURERS' PROFESSIONAL COMMITMENT - Anwar, Saiful; Utaminingsih, Sri; C. Bien, Jonna Karla; Nurlaili, Lili (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2024)
The variation in lecturers' commitment is the central issue addressed in this research. Based on the result of a preliminary study and data from the personal department. This fact is evidenced by the suboptimal performance of over 50% of permanent lecturers registered under the foundation fulfilling the three pillars of higher education. This study aims to analyze how the quality of work-life influences fluctuations in lecturers' professional commitment and how organizational culture also affects the level of commitment among tenure-track lecturers at Pamulang University. The quantitative research method uses data analysis through Structural Equation Modeling (SEM) and SITOREM analysis. The instruments used include questionnaires and expert judgment assessment sheets for SITOREM analysis. Upon data analysis, the following results were obtained: 1) the quality of work life significantly influences lecturers' professional commitment; 2) the organizational culture affects lecturers' professional commitment; 3) there is a simultaneous influence of both the quality of work life and organizational culture on lecturers' commitment to their profession. Based on the research findings, organizational culture, which constitutes a component of the organizational mechanism, exerts a direct influence on professional commitment, which is part of individual outcome theory, without necessitating passage through the variables encompassed within the individual mechanism. The implication of this study suggests that the professional commitment of lecturers can be further enhanced through the reinforcement of work-life quality and organizational culture. Abstrak: Bervariasinya komitmen dosen menjadi inti permasalahan dalam penelitian ini. Fakta ini dibuktikan berdasarkan studi pendahuluan dan data dari bagian kepegawaian bahwa lebih dari 50% dosen yang terdaftar sebagai dosen tetap yayasan belum optimal dalam menjalankan tridarma perguruan tinggi. Penelitian ini memiliki tujuan untuk menganalisis bagaimana kualitas kehidupan kerja memiliki pengaruh terhadap naik dan turunnya komitmen profesi dosen serta bagaimana budaya organisasi juga mempengaruhi tinggi rendahnya komitmen terhadap profesi dosen tetap yayasan di Universitas Pamulang. Metode penelitian yang digunakan adalah kuantitatif dengan analisis data menggunakan SEM dan analisis SITOREM. Instrument yang digunakan adalah angket dan lembar penilaian expert judgment untuk analisis SITOREM. Setelah dilakukan analisis data maka diperoleh hasil sebagai berikut 1) kualitas kehidupan kerja memiliki pengaruh terhadap pada komitmen profesi dosen; 2) budaya organisasi memiliki pengaruh terhadap komitmen profesi dosen; 3) terdapat pengaruh secara simultan kualitas kehidupan kerja dan budaya organisasi terhadap komitmen terhadap profesi dosen. Berdasarkan hasil penelitian, maka budaya organisasi yang merupakan bagian dari organizational mechanism memiliki pengaruh secara langsung terhadap komitmen profesi yang merupakan bagian dari teori individual outcome tanpa perlu melalui variabel yang tercakup pada individual mechanism. Implikasi pada penelitian ini dikemukakan bahwa komitmen profesi dosen dapat terus ditingkatkan melalui penguatan kualitas kehidupan kerja dan budaya organisasi.